Inverted South Trilogy: creation of theatrical texts based on perspectives of the south region of Rio Grande do Sul (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article discusses the starting point for the creation of the theatrical texts for the Inverted South Trilogy: southern Rio Grande do Sul, a Brazilian state. By observing the three plays and their respective genesis, it is possible to see how this region is used as the background of the works comprising the trilogy. The collection, written by Ingrid Duarte, Mario Celso, and Thalles Echeverry, professors graduated from the Universidade Federal de Pelotas, was launched during the COVID-19 pandemic with resources granted according to Federal Law n.º 14017 (Aldir Blanc Law). This trilogy highlights a change in perspective which goes beyond the capital of the state to address cities located outside the metropolitan areas, and demonstrates the importance of creating spaces for training and incentive to writing of plays, particularly to new authors.
Keywords: Theatrical text; dramaturgy; brazilian theater; Rio Grande do Sul